AI in enhancing cultural sensitivity - Mariyono, Dwi; Abror, Mufidul (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This study investigates the role of Artificial Intelligence (AI) in promoting multicultural sensitivity and inclusivity in education. Using the PRISMA framework, 71 primary articles were analyzed from ERIC, ProQuest, Scopus, and Web of Science. Findings indicate that AI-based instructional media outperform conventional methods in improving cultural representation and reducing implicit biases. However, challenges such as algorithmic bias and unequal access persist, underscoring the need for ethical frameworks and culturally responsive pedagogies. This research highlights AI's potential to foster adaptive learning environments, enhance engagement, and address educational inequalities. Recommendations emphasize the importance of ethical AI implementation to support equitable and inclusive practices in multicultural education.